Direct Measurements of Abdominal Visceral Fat and Cognitive Impairment in Late Life: Findings From an Autopsy Study - Nishizawa, Aline; Cuelho, Anderson; de Farias-Itao, Daniela S.; Campos, Fernanda M.; Leite, Renata E. P.; Ferretti-Rebustini, Renata E. L.; Grinberg, Lea T.; Nitrini, Ricardo; Jacob-Filho, Wilson; Pasqualucci, Carlos A.; Suemoto, Claudia K. (Frontiers in Aging Neuroscience, 2019)
Background: The relationship between cognitive impairment and abdominal visceral is controversial. Moreover, all studies so far used imaging studies to evaluate visceral fat and this association has not been described yet using autopsy material, which allows the direct quantification of abdominal fat. We aimed to investigate the association between direct measurements of abdominal visceral fat and cognitive impairment in an autopsy study. Methods: In this cross-sectional study, we collected information on sociodemographics, cardiovascular risk factors, and cognitive status from subjects aged 50 or older at time of death in a general autopsy service in Brazil. Abdominal visceral fat was obtained in natura by the dissection of perirenal, mesenteric, omental, and mesocolon fat. The associations of total abdominal visceral fat with cognitive impairment [Clinical Dementia Rating (CDR) score ≥0.5) and CDR-sum of boxes (CDR-SB) were evaluated using logistic regression and negative binomial regression models, respectively. All analyses were adjusted for height, age, sex, education, hypertension, diabetes mellitus, stroke, smoking, alcohol use, and physical inactivity. In addition, we compared the discrimination of visceral fat, body mass index (BMI), and waist circumference (WC) measurements in predicting cognitive impairment. Results: We evaluated 234 participants (mean age=71.2±12.9 years old, 59% male). Abdominal visceral fat was inversely associated with cognitive impairment (OR=0.46, CI=0.30; 0.70, p<0.0001) and with CDR-SB scores (β=-0.85, 95% CI=-1.28; -0.43, p<0.0001). When we compared the area under the ROC curve (AUC), visceral fat (AUC=0.754), BMI (AUC=0.729), and WC (AUC=0.720) showed similar discrimination in predicting cognitive impairment (p=0.38). Conclusion: In an autopsy study, larger amount of directly measured abdominal visceral fat was associated with lower odds of cognitive impairment in older adults.